ETHICAL VALUES IN ISLAMIC ECONOMICS: A CONCEPTUAL AND LITERATURE-BASED ANALYSIS - Yulinar Dhian Syafitri; Nayssella sepdikha Yanti (SHACRAL: Shari'ah Economics Review Journal, 2025)
Islamic economics is fundamentally rooted in ethical and moral values derived from the Qur’an and Sunnah, positioning it as a normative-economic system that integrates material welfare with spiritual and social objectives. In recent decades, the growing interest in Islamic finance and halal industries has not always been accompanied by a proportional internalization of ethical values, leading to a widening gap between normative ideals and practical implementation. This article aims to systematically review and conceptually analyze the ethical foundations of Islamic economics and their relevance in addressing contemporary economic challenges. Employing a qualitative literature review approach, this study synthesizes classical Islamic economic thought, contemporary scholarly works, and empirical findings from previous studies without relying on primary data. The review focuses on key ethical principles such as justice (ʿadl), balance (tawāzun), responsibility (mas’ūliyyah), transparency, and social welfare (maṣlaḥah), and examines how these values are operationalized within modern economic practices. The findings indicate that ethical values are not merely complementary elements but constitute the core epistemological and axiological foundations of Islamic economics. However, the literature also reveals persistent challenges in translating these values into institutional frameworks, regulatory mechanisms, and business behavior, particularly in Muslim-majority countries experiencing rapid economic transformation. Practical phenomena such as inequality, ethical lapses in financial institutions, and the dominance of profit-oriented motives underscore the urgency of re-centering ethics in Islamic economic discourse. By integrating insights from international and Indonesian contexts, this article contributes to the enrichment of Islamic economic literature, particularly for policy formulation and academic discourse at the national level. The study concludes that strengthening ethical values through education, governance, and regulatory alignment is essential to ensuring that Islamic economics fulfills its moral and socio-economic objectives.